The sea of monsters - Riordan, Rick (Riordan, Rick. Percy Jackson & the Olympians, 2022)
When Percy Jackson, a seventh-grade demigod living in New York, learns from his friend Annabeth that someone has poisoned the magical borders that protect Camp Half-Blood, Percy and his friends must journey into the Sea of Monsters to save their camp.